Factor analysis of a motivation questionnaire adapted to predoctoral French dental students - Laurent Deumier; Brigitte Alliot-Licht; Ludivine Bouton-Kelly; Angélique Bonnaud-Antignac; Christophe Michaut; Florence Quilliot; Gilles Guihard (Elsevier, 2016)
Background/purpose: The motivations of dental students for their studies have largely been investigated in numerous countries using psychometric questionnaires. This is not the case in France since validated tools are still lacking. The aim of the present work was dedicated to the psychometric validation of a motivation questionnaire adapted for predoctoral French dental students. Material and methods: The design corresponded to a monocentric study realized at the dental school of Nantes University, France. A 14-item questionnaire was translated into French and adapted for dental studies. It was autoadministered by the students between March 2014 and May 2014. Exploratory and confirmatory factorial analyses were used to investigate the psychometric properties of the French version. Results: The rate of reply was 88.7% with a sex allocation consisting of 44.4% men and 55.6% women. The internal reliability and the item-sampling adequacy of the questionnaire reached acceptance thresholds. Exploratory and confirmatory factorial analyses established a four-factor structure with good internal reliability. The factors consisted in "altruism," "status and incomes," "scientific curiosity," and "educational advantages." Factors correlated well with the overall questionnaire. The overall motivation score did not differ between male and female students, although "altruism" was best scored by female students while "status and incomes" obtained a higher score in the population of male students. Both male and female students displayed similar "scientific curiosity" and "educational advantages" scorings. Conclusion: Our data establish that the French motivation questionnaire has good psychometric properties and that it is relevant for further studies.